2023
DOI: 10.3390/agriculture13010139
|View full text |Cite
|
Sign up to set email alerts
|

Smart Detection of Tomato Leaf Diseases Using Transfer Learning-Based Convolutional Neural Networks

Abstract: Plant diseases affect the availability and safety of plants for human and animal consumption and threaten food safety, thus reducing food availability and access, as well as reducing crop yield and quality. There is a need for novel disease detection methods that can be used to reduce plant losses due to disease. Thus, this study aims to diagnose tomato leaf diseases by classifying healthy and unhealthy tomato leaf images using two pre-trained convolutional neural networks (CNNs): Inception V3 and Inception Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The adapted technique was trained and validated using the Plant-Village database, with the obtained results achieving an accuracy of 99.51% for 3 tomato disease classes, 98.65% for 5 tomato disease classes, and 97.11% for 10 tomato classes. A smart approach has been proposed in [12] using pre-trained Inception Version 3 and ResNet Version 2 networks to classify tomato diseases. The most important accuracy results obtained were 99.22% with specific configurations for the pre-trained models Inception V3 and ResNet V2 with a 50% and 15% dropout rate respectively.…”
Section: Related Workmentioning
confidence: 99%
“…The adapted technique was trained and validated using the Plant-Village database, with the obtained results achieving an accuracy of 99.51% for 3 tomato disease classes, 98.65% for 5 tomato disease classes, and 97.11% for 10 tomato classes. A smart approach has been proposed in [12] using pre-trained Inception Version 3 and ResNet Version 2 networks to classify tomato diseases. The most important accuracy results obtained were 99.22% with specific configurations for the pre-trained models Inception V3 and ResNet V2 with a 50% and 15% dropout rate respectively.…”
Section: Related Workmentioning
confidence: 99%
“…Batch normalization layer to speed up the training of deep neural networks, batch normalization attempts to minimize internal covariate shift. This is done by fixing the means and variances of the input layer layers during a normalization stage (Saeed et al, 2023). The following equations describe the calculation for BN operation: 1) Determine the mean of mini-batch (ℬ)…”
Section: Transfer Learning (Pre-trained Models)mentioning
confidence: 99%
“…Using a pre-trained VGGNet model, they achieved an accuracy of 91.83% for recognizing the diseases available in the PlantVillage dataset, while the accuracy of identifying examples within the self-collected database was 92.00%. Saeed et al [25] used two pretrained CNNs, InceptionV3 and InceptionResNetV2, which were trained on 5225 images from the PlantVillage dataset [21] to classify healthy and unhealthy tomato leaves. They investigated the impact of using different dropout rates and concluded that the best results were achieved using InceptionV3 with a 50% dropout rate and InceptionResNetV2 with a 15% dropout rate, with an accuracy of 99.22%.…”
Section: Related Workmentioning
confidence: 99%